Personal Financial Behavior and Financial Life Cycle: Evidence from Indonesia - Yuliani,; Maharini Adiandari, Ade (International Journal of Psychosocial Rehabilitation, 2020)
Personal financial planning is a trend nowadays. Personal financial planning is related to someone's behavior to manage to finance depend on stated objectives. Personal financial behavior is measured by six dimensions. There are emergency funds, debt level, savings rates, asset diversification, retirement preparation, and wealth distribution. This study aims to analyze the relationship between personal financial behavior and the financial life cycle. The financial life cycle based on age consists of three stages, namely the stage of accumulating wealth, namely the age of 20-40 years, the stage of multiplying wealth, namely the age of 41-50 years, and the stage of distributing wealth, which is 51 years and above. Sampling criteria are respondents who have worked and have income. 203 respondents from Indonesia as research subjects with questionnaire data collection periods from the second week of January to the first week of March 2019. Test instruments have met the reliability and validity test criteria. Testing with Chi-Square in answering the hypothesis. The results of the study found that there was a significant relationship between the preferences of respondents about emergency funds based on the financial life cycle. The dimensions of savings rates, debt level, retirement preparation, asset diversification, and wealth distribution for respondents do not have a significant relationship based on the financial life cycle. Research contributions in theory show that understanding the importance of personal financial management planning is one of the topics in financial management, especially personal finance behavior. Management finance behavior theory observes a personal behavior in planning to finance so that it prepares for financial freedom in old age. Practically, the contribution of this research is needed for every individual who has financial goals in old age.